Dasa Manis Sugar Marketing Strategy In Increasing PTPN X Product Sales Volume: Strategi Pemasaran Gula Dasa Manis Dalam Meningkatkan Volume Penjualan Produk PTPN X - Suhariadi, Arif; Rizal, As'at (Universitas Muhammadiyah Sidoarjo, 2022)
In this era, the business world has experienced very rapid development. Sugar is one of the strategic commodities for the Indonesian economy, because it is one of the nine basic ingredients commonly consumed by the people of Indonesia. The purpose of this study was to determine the marketing strategy and marketing strategy position of Sugar Dasa Manis products in increasing sales volume. This research uses descriptive qualitative method. The research location chosen by the researcher is located at Jl. Red Bridge No.3-11, Krembangan Sel., Kec. Krembangan, Surabaya City, East Java. The type of data taken in this study uses qualitative data, namely primary data and secondary data. Data collection techniques used are interviews, documentation, and observation. While the sampling technique used is the Non-Probability Sampling technique. The data that has been obtained is then analyzed using Smart PLS 3.2.7 Software. Based on the results of the study, it can be concluded that the quality of the products marketed must be maintained such as the color of sugar, attractive and dry packaging, always available when consumers need it, and determine the expected market segment.